Performance Pedagogy: Transmitting Cultural Memory Through Music Education In Diverse Societies - Shevchenko, Liliia; et al. (European Journal of Social Science Education and Research, 2026)
In diverse societies, music education is becoming a means of dialogue between generations and cultures and an effective tool for preserving cultural identity. Today, performance pedagogy is entrusted with not only developing the musician’s technical skills but also transmitting cultural memory. In the context of this study, the phenomenon of cultural memory is understood as a set of values, traditions, intonation codes, and historical experiences accumulated through music. The main objective of the study was to analyze how music education curricula can include performance to promote cultural understanding. The current study conceptualizes music performance pedagogy as the primary medium through which cultural memory is encoded, shaped, and transformed. Adopting a qualitative approach based on an interpretivist epistemology, the study draws on systematic secondary research in musicology, performance studies, cultural memory theory, and the digital humanities. Through thematic and comparative analyses, it consolidates understanding of embodiment, repetition, canonical structures, and digital mediation in music performance pedagogy. The study emphasizes the role of music performance educators as curators of cultural memory and the need to tap into the potential of hybrid live-digital spaces as new archival environments. These findings have implications for contemporary pedagogical practice, demonstrating that performance not only preserves but also actively reshapes cultural memory in both the physical and digital spheres.